THE EFFECTIVENESS OF ULTRASOUND TREATMENT IN MYOFASCIAL PAIN SYNDROME - Selda Kısaoğlu,; H. Rana Erdem,; Gönül Göncü,; Z. Rezan Yorgancıoğlu, (Archives of Rheumatology, 2000)
Myofascial pain syndrome (MPS) is a skeletal muscle disorder vvhich is characterized by taut bands in one or more muscle groups and hypersensitive referred pain areas from these bands called trigger points. Primary aim of the treatment is to interrupt the pain cycle by inactivating the trigger points. The purpose of this study is to evaluate the efficacy of ultrasound therapy by using objective parameters in MPS. Forty female patients with the diagnosis of MPS were included in this study (mean age 30 ± 8,4 years) and patients were randomly distributed into two equal groups. Hotpack and ultrasound therapy were applied to the first group (ultrasound treatment group) and only hotpack was applied to the second group (control group). Duration of therapy was 10 days for both groups. İn ultrasound treatment group the increase in pressure pain threshold and tissue compliance values (p<0,05) and the decrease in VAS values (p<0,05) were statistically significant after the therapy. Though a little increase in the tissue compliance and pressure pain threshold values in the control group was detected, it vvasn't statistically significant (p>0,05). İn the comparison of two groups, alterations in VAS, tissue compliance and pressure pain threshold values were statistically more significant in ultrasound treatment group (p<0,05). As a result we determined the efficacy of ultrasound treatment vvhich is one of the counterstimulation techniques that can sometimes be used in MPS treatment, by using objective parameters and suğgested this technique as an important choice in appropriate cases.